Entomology in country schools - Phipps, William H. (My University, 1895)
Introduction: Western civilization claims to surpass the old in free institutions, and in all that permits the fullest and truest development of all human possibilities into the most perfect results. Out of our educational institutions grow the highest and the grandest achievements of the present age. This pedestal that supports “Liberty’s Station” is our public schools. Free and universal education is the only way to free government. Intelligent American youth insures the noblest citizenship and the safety, stability, and perpetuity of our nation. If evils and dangers threaten, if discontent and anarchy culminate in dissention and revolution, our schools are to blame. How important, then, that our boys and girls should find in the common schools that which will help them to become good citizens and to most grandly live. That our public schools at the present time are not doing for American youth what they should do is evident to all who will think.
Citation: Phipps, William H. Entomology in country schools. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Education; Country schools; Entomology; Theses; Manuscripts (documents)